CORRUPTION AS ONE OF THE OBSTACLES IN FORMING THE PROFESSIONAL CULTURE OF PUBLIC SERVANTS - Zhovnirchyk, Yaroslav; Tymofieiev, Serhii (Public Administration and Regional Development, 2022)
The article is devoted to the complex and multifaceted process of forming the professional culture of public servants, which is accompanied by a number of problems of a socio-economic, political and cultural nature, one of which is widespread corruption. Based on the analysis, it was found that trust is the main criterion for the effectiveness of the entire public administration system, which indicates the ability of public servants to play the role of mediators between public authorities and representatives of society. It was determined that among the main reasons for the rather low level of professionalism of individual representatives of public servants, a significant number of citizens consider shortcomings in the work of recruiting personnel for the public service, the employment process "by acquaintance", as well as the acceptance of employees to managerial positions not on the basis of their professional qualities, but on personal relationship, which is a direct manifestation of corruption in the public service system of Ukraine. There is a constant interest in improving the qualifications of public officials on the topic of corruption prevention, which is due to both the high level of corruption and frequent changes in the regulatory and legal framework. It has been proven that the formation of a public official at the appropriate level of legal ideology is closely related to the implementation of the principle of legality, aimed at preventing bureaucracy and legal nihilism, which ultimately contributes to the humanization of public administration. A number of obstacles in the formation of the professional culture of public servants have been singled out, including: firstly, society perceives officials as serving their own interests, secondly, the bureaucratization of the power apparatus, thirdly, the lack of interest of citizens in participating in the improvement of the existing system of public administration, fourthly, the reluctance of a significant part of public servants to change something. The absolute problem of forming the professional culture of public servants is that the absolute overcoming of corruption is not possible, and therefore the only goal of combating corruption can be to reduce its level to a point that does not hinder the development of the country, society, economy, politics, and public administration.